The uptake of tau amyloid fibrils is facilitated by the cellular prion protein and hampers prion propagation in cultured cells. Issue 5 (26th June 2020) - De Cecco, Elena; Celauro, Luigi; Vanni, Silvia; Grandolfo, Micaela; Bistaffa, Edoardo; Moda, Fabio; Aguzzi, Adriano; Legname, Giuseppe
Abstract: Tauopathies are prevalent, invariably fatal brain diseases for which no cure is available. Tauopathies progressively affect the brain through cell‐to‐cell transfer of tau protein amyloids, yet the spreading mechanisms remain unknown. Here we show that the cellular prion protein (PrP C ) facilitates the uptake of tau aggregates by cultured cells, possibly by acting as an endocytic receptor. In mouse neuroblastoma cells, pull‐down experiments revealed that tau amyloids bind to PrP C . Confocal images of both wild‐type and PrP C ‐knockout N2a cells treated with fluorescently labeled synthetic tau fibrils showed that the internalization was reduced in isogenic cells devoid of the gene encoding PrP C . Pre‐treatment of the same cells with antibodies against N‐proximal epitopes of PrP C impaired the binding of tau amyloids and decreased their uptake. Surprisingly, exposure of chronically prion‐infected cells to tau amyloids reduced the accumulation of aggregated prion protein and this effect lasted for more than 72 hr after amyloid removal. These results point to bidirectional interactions between the two proteins: while PrP C mediates the entrance of tau fibrils in cells, PrP Sc buildup is greatly reduced in their presence, possibly because of an impairment in the prion conversion process. Abstract : We propose the following interplay between tau and the prion protein in the brain: the direct binding of tau amyloids to the physiological form of the prion protein (PrP C ) facilitates the cellular uptake of the amyloids, which in turn increase the levels of PrP C probably by interfering with its degradation. Tau amyloids hamper also the conversion of PrP C into its pathogenic conformer PrP Sc . This effect is independent of the prion strain and proceeds through the promotion of the α‐cleavage of PrP C, which disrupts the region of the prion protein essential for the conversion.